Checklist of Inland Aquatic Amphipoda (Crustacea: Malacostraca) of California - Graening, G. O.; Rogers, D. Christopher; Holsinger, John R.; Barr, Cheryl; Bottorff, Richard (Zootaxa, 2012)
We present the first comprehensive checklist of Amphipoda in Californian inland waters. Amphipod distributionrecords were based upon a thorough literature review and unpublished data of colleagues, as well as the collectionsof the authors. We report 62 species in 24 genera and 14 families, including 7 new taxa awaiting formal description.Sixteen species are exotic and at least 20 species are subterranean obligates. Endemicity is high: 40% of the nativefauna are limited to a single locale, typically a spring or cave stream, and another 3 species are known from just 2locales each. Conservation status rank revisions are offered in order to update the California Natural Diversity Da-tabase and IUCN Red List. Threats from invasive species are briefly discussed, as well as the use of amphipods as bioindicators.